Differential Expression of Syntaxin 1A and 1B by Noradrenergic and Adrenergic Chromaffin Cells - Baltazar, Graça (2003)
The expression and localization of syntaxin isoforms 1A and 1B in adrenergic and noradrenergic chromaffin cells were examined by both immunoblot analysis and confocal immunofluorescence microscopy. Syntaxin 1A was found in higher levels in noradrenergic cells, whereas syntaxin 1B was similarly expressed in most noradrenergic and adrenergic cells. However, some heterogeneity was observed within each catecholaminergic phenotype. Although the majority of adrenergic cells appeared to express low levels of syntaxin 1A, about 7% was strongly stained for syntaxin 1A. A subpopulation of noradrenergic cells, about 17%, expressed greater levels of syntaxin 1B. Syntaxin 1B labeling showed a punctate appearance in the cytoplasm, whereas syntaxin 1A appeared predominantly localized to the plasma membrane. These data show differences in the exocytotic machinery of the two subtypes of chromaffin cells that may underlie some of the distinct characteristics of adrenaline and noradrenaline secretion.